Genetic Relationship of Fall Armyworm (Spodoptera frugiperda) Populations That Invaded Africa and Asia - Rajendra Acharya; Ashraf Akintayo Akintola; Matabaro Joseph Malekera; Patrick Kamulegeya; Keneth Benedictor Nyakunga; Munyaradzi Kennedy Mutimbu; Yam Kumar Shrestha; Jahan S. M. Hemayet; Trinh Xuan Hoat; Hang Thi Dao; Jeong-Hoon Park; Iksoo Kim; et al. (Insects, 2021)
The fall armyworm, Spodoptera frugiperda, is an important agricultural pest native to tropical and subtropical regions of the Western Hemisphere, and has invaded Africa and further spread into most countries of Asia within two years. Here, we analyzed the genetic variation of invaded populations by comparing the nucleotide sequences of two genes: the nuclear Z-chromosome linked gene triose phosphate isomerase (Tpi) and the mitochondrial gene cytochrome oxidase subunit I (COI) of 27 specimens collected in Africa (DR Congo, Tanzania, Uganda, and Zimbabwe) and Asia (Bangladesh, Korea, Nepal, and Vietnam). The results revealed that 25 specimens were from a heterogeneous hybrid (Tpi-corn strain and COI-rice strain; Tpi-C/COI-R) of the corn strain male and rice strain female, but two specimens were from a homogenous corn strain (Tpi-corn strain and COI-corn strain; Tpi-C/COI-C). The further analysis of the fourth exon and the fourth intron sequences of the Tpi gene identified at least four subgroups of the corn strain. These four genetic subgroups were identified in Africa and Asia, suggesting no significant genetic change due to the rapid migration within two years. Our study provides essential information for understanding the genetic diversity of fall armyworm in new habitats.